Do Urban House Prices Converge?. Issue 2 (2nd April 2016) - Wood, Gavin; Sommervoll, Dag Einar; de Silva, Ashton
Abstract : We investigate two aspects of housing market price dynamics. Firstly, whether the spatial pattern of house prices in a metropolitan housing market converge or diverge over time and secondly, whether suburbs with relatively low (high) house prices 20 years ago continue to occupy the same relative position in the house price distribution. The empirical work uses a property transaction database for Melbourne to examine the changing distribution of suburban house prices over a nearly 20-year period (1990–2009) that spans two housing cycles. We focus on convergence measures that use Melbourne submarket-based repeat sale house price indexes as a unit of measurement. We find that house prices diverge, and so the gap between low-priced submarkets and high-priced submarkets is increasing. A second key result is that low-priced submarkets typically remain at the low end of the house price distribution, because their rates of appreciation fall short of those at the upper end of the house price distribution. The geography of house price dynamics suggests that the price gradient with respect to distance from the central business district is becoming steeper.